Fatores condicionantes na gestão da inovação em empresas de incubadoras tecnológicas na cidade de Curitiba - Paraná - Sauka, Jean Elizeu (2016)
Innovation-promoting environments have been shown to contribute significantly to the development of new companies. The discussion of issues surrounding Innovation in technological incubators has grown both in the academic literature and in corporate practice, where Innovation has been developing over time, with shifting boundaries and a growing body of frameworks and techniques. Thus, the objective of this study is to identify conditioning factors in the Innovation Management process in technology companies incubated in the city of Curitiba, in Paraná, Brazil. We carried out an exploratory study of nine organizations in four technology incubators, seeking to understand the details of Innovation Management in small incubated companies. We gathered data by having the managers of these businesses answer questionnaires with Likert-Scale questions. Our findings indicate that these organizations implement innovative actions and techniques in the course of their business, and we find that these small businesses do so in a particular manner that is geared towards the day-to-day activities of their team-members, thereby maintaining a continuous and dynamic process of innovation. This, in turn, results in superior problem-solving, business improvement and market performance. The internal and external transformations occur gradually, requiring that organizations actively and constantly adapt to market changes, with emphasis on their own human resources, specifically in terms of their defining characteristics, access to information, needs and capacity for effective action.